A framework for battery temperature estimation based on fractional electro-thermal coupling model. (July 2023) - Liu, Shichuang; Sun, Huanwu; Yu, Haotong; Miao, Jian; Zheng, Cao; Zhang, Xiuwei
Abstract: The temperature significantly affects the performance and safety of the battery. Therefore, this paper presents a novel framework for the estimation of the battery temperature based on a fractional-order electro-thermal coupling model. Due to the nonlinearity, coupling, and time varying parameters of lithium-ion batteries, the fractional-order equivalent circuit model is established using the fractional-order differential theory. Then it couples with the thermal model to establish the fractional order electro-thermal coupling model of lithium battery. Based on the model, the hybrid pulse power characteristic test method and the electro-thermal balance experiment are used to identify the parameters of the fractional order electro-thermal coupling model of lithium batteries. Finally, the fractional-order electro-thermal coupling model is used to estimate battery voltage, state of charge, and temperature under the conditions of the hybrid pulse power characteristic and the world transient vehicle cycle. The results show good consistency and responsiveness with the experiment under steady and dynamic conditions, and compared with the ETM, the characteristics of small error and low error rates of the F-ETM are introduced. Therefore, the fractional electrothermal coupling model of lithium batteries has good accuracy and applicability. Highlights: A fractional electro-thermal coupling model of lithium-ion battery is established for estimating the temperature. The fractional electro-thermal coupling model includes a fractional-order equivalent circuit model and a thermal model. High surface temperature estimation accuracy under the steady and the dynamic conditions.